Gaps in Administrative and Legal Regulation of the Liability Institution for Direct Contempt - H. P. Shust; O. S. Khovpun; O. V. Batryn (Bulletin of Kharkiv National University of Internal Affairs)
The publication is focused on studying the state of legal regulation of the liability institution for direct contempt. Cases of direct contempt’s manifestation are negative phenomenon, since they negatively affect the activities and image of the judicial system; they are demonstration of the level of trust to the judicial power; they create obstacles in the formation of confident relationship between citizens and the court; they prevent the state from fulfilling its obligations to ensure everyone’s right to a fair trial.